THE BODY-EARTH-TERRITORY: DIALOGUE BETWEEN GEOGRAPHICAL KNOWLEGDE AND FOUCALTIAN PHILOSOPHY - Antonello, Ideni Terezinha [UNESP]; Oliveira, Ariel Pereira da Silva (Univ Federal Mato Grosso Sul, 2022)
This article has as its main goal to highlight the aspects of Foucault thoughts that are bound to be applied in theoretical-conceptual discussions about the body-earth-territory, that has become stronger in the geographical studies of this genre, especially in Latin America. The present reflection is structured in two main parts: in the first part the influenced of Foucault in Geography is discussed, predominantly the incorporation of the genre studies and their conception of power in the analysis concerned to the territory concept. In the second part some arguments of the French philosopher that are probably incorporated and articulated in the body-earth-territory, which is being strengthened, will be retrieved. They are also strengthening the genre studies in Latin-American Geography. This article constitutes in a theoretical essay, thus, the methodology used, was a bibliographical review which allowed the understanding the impact of Foucault thought had in Geography, as well as its potentiality for new themes that challenges to think about the processes and spatial multi-scale phenomena, which are not unrelated to the body dimension. It was observed how the Foucauldian interpretation provides a basis for intrinsically shrouded thematic with the geographical worries. What calls for an analysis for the knowledge-power-space linking, primarily the power over space (body-earth-territory).
Keywords: Corporealities; Geography; Michael Foucault